48.9k views
3 votes
Please help, thank you

Please help, thank you-example-1
User Hagne
by
4.9k points

2 Answers

1 vote

Answer:

The sum = 4092

Explanation:

The sum is equal to A, in which:

A = 4 x (2^0 + 2^1 + 2^2 + ... + 2^9)

= 4 x [(1 + 2^1 + 2^2 + ... + 2^9)(2 - 1)/(2 - 1)]

= 4 x (2^10 - 1)(2 - 1)

= 4 x (2^10 - 1)

= 4 x 1023

= 4092

Hope this helps!

User Uri London
by
5.2k points
3 votes

Answer:

4092

Explanation:

The n th term of a geometric sequence is


a_(n) = a
r^(n-1)

where a is the first term and r the common ratio

4
(2)^(n-1) ← is the n th term of a geometric sequence

with a = 4 and r = 2

The sum to n terms of a geometric sequence is


S_(n) =
(a(r^(n)-1) )/(r-1) , thus


S_(10) =
(4(2^(10)-1) )/(2-1) = 4(1024 - 1) = 4 × 1023 = 4092

User Yellen
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.